THE EFFECT OF DIFFERENTIATED LEARNING OF PARENTAL INVOLVEMENT AND LEARNING STYLE ON SOCIAL STUDIES LEARNING SKILLS STUDENTS OF SD NEGERI MAYANGAN 2 - Try Novita Devi, Maristha; Ifana Sari, Yuli; Farida Ni’matullah, Onik (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to examine the impact of differentiated instruction, parental involvement, and learning styles on the Social Studies learning skills of sixth-grade students at SD Negeri Mayangan 2 in Probolinggo City. The research employs a quantitative approach with a survey design, collecting data through questionnaires distributed to students, parents, and teachers. The sample consists of 73 students, selected using a saturated sampling technique. The data were analyzed using descriptive statistics and multiple regression analysis. The results indicate that differentiated instruction, parental involvement, and learning styles have a significant influence on students' Social Studies learning skills. Differentiated instruction supports students in developing critical thinking and creativity, while parental involvement enhances student motivation and discipline. Additionally, understanding students' learning styles enables teachers to adapt their teaching methods effectively. These findings emphasize the importance of collaboration among teachers, parents, and students in fostering an inclusive and adaptive learning environment. This approach not only enhances students' ability to comprehend Social Studies content but also has a positive impact on their academic performance. The study contributes to the development of teaching strategies that are more focused on addressing the individual needs of students.